(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa generale: il quadro normativo di riferimento - 2. Un’intesa particolare - 3. La certificazione dell’idoneità diocesana - 4. La riserva dei posti messi a bando - 5. Il programma d’esame - 6. La composizione delle commissioni giudicatrici - 7. Conclusioni. A particular agreement: procedural elements not agreed upon next contest for teachers of the Catholic religion ABSTRACT: This paper aims to examine the agreement signed on December 14, 2020 between the Minister of Education and the President of the Italian Bishops’ as an act prior to a contest for teachers of the Catholic religion. In light of the previous agreements and some specific studies, the author attempts to highlight how some elements of State competence have merged into a procedural act, wondering if this represents an overrun of the respective prerogatives.